2007
DOI: 10.1016/j.febslet.2007.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid is an essential moiety of mucin as a hydroxyl radical scavenger

Abstract: In this work, we examined the antioxidant role of mucin, a typical sialic acid containing high-molecular weight glycoprotein. The function of mucin as a hydroxyl radical ( Å OH) scavenger was characterized using bovine submaxillary gland mucin (BSM). Non-treated BSM effectively protected DNA from the attack of Å OH; however, desialylated BSM lost this potential. Moreover, we estimated the scavenging effects of BSM against Å OH generated by UV irradiation of hydrogen peroxide using ESR analysis. Our results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 27 publications
2
65
1
3
Order By: Relevance
“…Presently, studies investigating the correlation between serum total sialic acid and the severity of atherosclerosis have presented conflicting results. It is noteworthy that recent studies have demonstrated that sialic acid could scavenge ROS 13, 14, 15 and may be applied as therapeutic option in some diseases 16, 17, 18.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, studies investigating the correlation between serum total sialic acid and the severity of atherosclerosis have presented conflicting results. It is noteworthy that recent studies have demonstrated that sialic acid could scavenge ROS 13, 14, 15 and may be applied as therapeutic option in some diseases 16, 17, 18.…”
Section: Introductionmentioning
confidence: 99%
“…One of important functions of sialic acid is 'molecular mimicry', in which successful microbial pathogens decorate themselves with sialic acids, assisting in evasion of host immunity (Vimr et al 2004). Mucin, which contains high-molecular-weight glycoprotein (containing sialic acid), functions as hydroxyl radical scavenger and loses its ability when desialylated; thus mucin has the ability to protect cells from oxidants (Ogasawaraa et al 2007). Since oxidative stress is known to increase with age in humans (Rizvi & Maurya 2006, 2007 and our present results also substantiate this in rats, we presume that loss of sialic acid could also contribute to decreased ability of mucin to protect against oxidants.…”
Section: Resultsmentioning
confidence: 99%
“…The most common member of this group is N-acetylneuraminic acid (NANA). Sialylated conjugates in mammals perform important roles in cellular recognition, signalling, hydroxyl radical scavenging, neuronal development and host-pathogen interaction (Ogasawaraa et al 2007;Varki 2008). Sialic acids are also the ligands for the Siglec family of cell adhesion molecules, which appear to be involved in regulating the immune response (Varki & Angata 2006;Crocker et al 2007;Varki 2007).…”
Section: Introductionmentioning
confidence: 99%
“…18) Tris(2,2Ј-bipyridine)ruthenium(III), or Ru(bpy) 3 3ϩ , has been shown to be an important chemiluminescence reagent. When coupled with flow injection analysis (FIA), 19) 3 3ϩ and · OH are in contact in the spiral cell in the detector, and thus, the chemiluminescence is continuously maintained. Constant chemiluminescence is generated and recorded as the background emission.…”
Section: Notesmentioning
confidence: 99%
“…When · OH is generated in excess and the cellular antioxidant defense is deficient, some free radical chain reactions can attack proteins, lipids, and nucleic acids, leading to cellular damage. [1][2][3] Living systems contain complex enzymatic antioxidants such as superoxide dismutase, glutathione peroxidase, and catalase. These enzymes can block the initiation of · OH and the free radical chain reaction.…”
Section: Notesmentioning
confidence: 99%